Wind speed and solar irradiance forecasting techniques for enhanced renewable energy integration with the grid: a review. Issue 7 (1st August 2016) - Ssekulima, Edward Baleke; Anwar, Muhammad Bashar; Al Hinai, Amer; El Moursi, Mohamed Shawky
Abstract : Power generation from renewable energy resources is on the increase in most countries, and this trend is expected to continue in the foreseeable future. In an effort to enhance the integration of renewable power generation from solar and wind into the traditional power network, there is need to address the vulnerabilities posed to the grid as a result of the intermittent nature of these resources. Variability and ramp events in power output are the key challenges to the system operators due to their impact on system balancing, reserves management, scheduling and commitment of generating units. This has drawn the interest of utilities and researchers towards developing state of the art forecasting techniques for forecasting wind speeds and solar irradiance over a wide range of temporal and spatial horizons. The main forecasting approaches employ physical, statistical, artificial intelligence and hybrid methodologies. This study provides the rationale for forecasting in power systems, a succinct review of forecasting techniques as well as an assessment of their performance as applied in the literature. Also, techniques for improving the accuracy of forecasts have been presented together with key forecasting issues and developing trends.